2004
DOI: 10.1128/mcb.24.14.6514-6524.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mcm1 Promotes Replication Initiation by Binding Specific Elements at Replication Origins

Abstract: Replication of DNA must be inherently accurate and precisely regulated. It is therefore not surprising that the mechanism for the initiation of DNA replication is both complex and conserved. Initiation of DNA synthesis involves the assembly of a multicomponent complex at designated sites known as replication origins. While the protein components of the prereplication complex (pre-RC) used in this initiation process are conserved in all eukaryotes (5), there is little in common between the nucleotide sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 76 publications
(74 reference statements)
1
30
0
Order By: Relevance
“…The original biological function of SRF appears to be that of a generic DNA-binding transcriptional activator important for expansion of cell populations, as the yeast SRF homolog MCM1 regulates DNA synthesis via binding DNA sequences near replication origins and by transcriptional activation of several cell-cycle control genes important for proliferative growth of this organism. 8 Indeed, this function has been evolutionarily conserved as SRF was so named because it was first found to regulate transcription of immediate early genes important for initiation of mitogenesis in response to the addition of serum into the media of various cultured mammalian cell lines. 9 It has been appreciated for quite some time that SRF homodimers perform this function via binding to CArG box DNA sequences within the promoters of immediate early genes (eg, c-fos) and forming a ternary complex with various serum-activated Ets-domain proteins (ie, the ternary factors [TCFs] Elk-1, Sap-1, Fli-1) that assist SRF in stimulating transcription of these genes.…”
Section: Transcriptional Control Of Smc Differentiation By Serum Respmentioning
confidence: 99%
“…The original biological function of SRF appears to be that of a generic DNA-binding transcriptional activator important for expansion of cell populations, as the yeast SRF homolog MCM1 regulates DNA synthesis via binding DNA sequences near replication origins and by transcriptional activation of several cell-cycle control genes important for proliferative growth of this organism. 8 Indeed, this function has been evolutionarily conserved as SRF was so named because it was first found to regulate transcription of immediate early genes important for initiation of mitogenesis in response to the addition of serum into the media of various cultured mammalian cell lines. 9 It has been appreciated for quite some time that SRF homodimers perform this function via binding to CArG box DNA sequences within the promoters of immediate early genes (eg, c-fos) and forming a ternary complex with various serum-activated Ets-domain proteins (ie, the ternary factors [TCFs] Elk-1, Sap-1, Fli-1) that assist SRF in stimulating transcription of these genes.…”
Section: Transcriptional Control Of Smc Differentiation By Serum Respmentioning
confidence: 99%
“…Therefore, it is only in combination that the A, B1 and B2 elements from ARS121 are sufficient to reduce the requirement for Mcm2–7 protein function. Binding sites for the Mcm1 transcription factor have been suggested to affect mcm sensitivity (49). We found that mutating three Mcm1 binding sites outside this region (Yp-CN13) did not significantly elevate the plasmid loss rate in mcm2-1 cells (data not shown), consistent with the finding that the resilience of ARS121 to reduced Mcm2–7 function is linked mainly to the A, B1 and B2 elements.…”
Section: Resultsmentioning
confidence: 99%
“…This phenotype could result from the role of Mcm1 in regulating the expression of pre-RC genes, including CDC6 , MCM3 , MCM5 , MCM6 and MCM7 (5658), or via a direct role for Mcm1 in pre-RC assembly (49). …”
Section: Resultsmentioning
confidence: 99%
“…Coupling via enzyme messengers probably also exists between replication hyperstructures and metabolic hyperstructures. In the yeast Saccharomyces cerevisiae, thousands of genes, including those involved in DNA replication, show periodic expression during an ultradian respiration/reduction cycle, while the S phase occurs during the reduction period of the cycle (121,263) and its completion strictly depends on glyceraldehyde-3-phosphate dehydrogenase through its role in stimulating the expression of histone genes (292); moreover, a key protein in replication, MCM1, is linked genetically to several glycolytic enzymes (44,46). In human cells, lactate dehydrogenase, phosphoglycerate kinase, and glyceraldehyde-3-phosphate dehydrogenase can be transported to the nucleus, where they can bind single-stranded DNA and, in vitro, modulate the activity of the replicative DNA polymerases Pol␣, Pol␦, and Polε (218,231,240); moreover, phosphoglycerate kinase is a cofactor of Pol␣ (108).…”
Section: Hyperstructures Send and Receive Messages Via Their Constitumentioning
confidence: 99%